Shapers of Islam in Southeast Asia - Aljunied, Syed Muhd Khairudin (Oxford University Press, 2022)
Glossary -- Introduction: Islamic Reformist Mosaic in Southeast Asia -- 1. Naquib Al-Attas: The Desecularist -- 2. Osman Bakar: The Epistemist -- 3. Harun Nasution: The Rationalist -- 4. Ahmad Ibrahim: The Legalist -- 5. Kuntowijoyo: The Historicist -- 6. Cesar Majul Adib: The Integrationist -- 7. Zakiah Daradjat: The Moralist -- Epilogue: Muslim Reformism and the Future of Islam -- Bibliography.